2008
DOI: 10.1111/j.1360-0443.2008.02140.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐help smoking cessation interventions in pregnancy: a systematic review and meta‐analysis

Abstract: Aims Self-help smoking cessation interventions for pregnant smokers are of importance due to their potential to be wide-reaching, low-cost and their appeal to pregnant smokers who are interested in quitting smoking. To date, however, there has been no systematic assessment of their efficacy. This systematic review aimed to assess the efficacy of self-help interventions for pregnant smokers and to investigate whether self-help material intensity, type or delivery are associated with cessation. Methods The liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 48 publications
0
43
0
3
Order By: Relevance
“…Precision estimates for detecting between‐group differences in quit rates were calculated for ranges of treatment effects [i.e. odds ratio (OR)] and usual care group quit rates 19 for example, these showed that if a 5% usual care group quit rate occurred in late pregnancy, with 400 participants the trial would estimate an OR of 1.8 (as noted in a previous review) 12 with 80% confidence intervals (CIs) of 1.06–3.05) 19.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Precision estimates for detecting between‐group differences in quit rates were calculated for ranges of treatment effects [i.e. odds ratio (OR)] and usual care group quit rates 19 for example, these showed that if a 5% usual care group quit rate occurred in late pregnancy, with 400 participants the trial would estimate an OR of 1.8 (as noted in a previous review) 12 with 80% confidence intervals (CIs) of 1.06–3.05) 19.…”
Section: Methodsmentioning
confidence: 99%
“…After undertaking the planned analyses, we decided to generate a Bayes factor from smoking outcome 1, using an online calculator 33 with an expected effect size of OR = 1.83 taken from a relevant systematic review 12. We used a conservative approach for estimation using a half‐normal distribution, where the mode at 0 indicated no intervention effect and the standard deviation equal to the expected effect size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking in pregnancy is the main preventable cause of poor birth outcomes, including miscarriage, stillbirth, prematurity and low birth weight 1, 2, 3, 4, 5, 6. Smoking also presents immediate risks for the mother, including placental abruption 7, as well as the long‐term risks reported for smokers in general.…”
Section: Introductionmentioning
confidence: 99%
“…229,230 The impact of brief advice in special populations (e.g. pregnant women, 216,231,232 adolescents, 233 patients with mental health problems, [234][235][236] ) is less clear. Providing support during a quit attempt increases the chance of success up to five-fold.…”
Section: Individual Smoking Cessation Supportmentioning
confidence: 99%